A percepção de egressos sobre as transformações curriculares ocorridas no curso de graduação em enfermagem - Maria Helena Salgado Bagnato; Giselle Cristina Martins Real; Márcia Maria Ribeira Lopes Spessoto (Universidade Estadual de Campinas, 2012)
This work has the objective to analyze the perception of the egre sses of nursing about the curricular changes of nursing graduation since 1990. It is deal with a qualitative search, which used a bibliographic survey, a documental analysis of content and the field research by questionnaire and the focal group, has been the support the analysis of the content. The egresses of the Universidade Estadual of Mato Grosso do Sul, graduated between 2004 and 2009, being three groups graduated under the curricular legislation from 1994, and three groups under the National Curricular Policies for the graduation course of nursing from 2001. In the results, the egresses distinguished their participation in doing the present Political Pedagogical Project of the course, besides to point out as the integrality and the curricular probation oversee. We believe this studies and discussions being to continue, including all of the authors of the process. Inferred that the curricular matrix of the course have been attempting the present curricular orientations, managing with nurses graduation a ble to the health policy. Hoping to contribute to the educational policies to suscitate reflections and debates about the the object.